2020
DOI: 10.1136/bmjopen-2020-038434
|View full text |Cite
|
Sign up to set email alerts
|

Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study

Abstract: ObjectivesHaving more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients’ needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…“Mobility (d4)” played a major role for the participants. This is in accordance with the findings from our empirical study, which is also part of the ICF Core Set development process ( 35 ). Mobility is central to healthy ageing and independent living ( 10 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…“Mobility (d4)” played a major role for the participants. This is in accordance with the findings from our empirical study, which is also part of the ICF Core Set development process ( 35 ). Mobility is central to healthy ageing and independent living ( 10 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…The preparatory studies from the four perspectives each yielded different numbers and kinds of candidate categories of the ICF with some overlap but also differences. The systematic review identified 87,19 the patients’ perspective 189,18 the clinical perspective 8716 and the experts’ perspective 6717 second-level categories. Table 1 shows the number of categories in each ICF component that were identified in the individual preparatory studies 16–19…”
Section: Resultsmentioning
confidence: 99%
“…The preparatory phase was conducted as part of the project ‘Preventing Overdiagnosis in Primary Care’ (PRO PRICARE, German Federal Ministry of Education and Research, grant number: 01GY1605). A detailed report on the methods and analysis from each of the four preparatory studies can be found in the corresponding scientific publications 16–19…”
Section: Methodsmentioning
confidence: 99%
“…As the ICF conceptualizes disability as a health experience that occurs in a context, every domain should be assessed to look at medical, individual, social, and environmental influences on functioning and disability [ 97 ]. Different categories of older adults’ functioning have been studied [ 98 , 99 ], and some relevant ones have been proposed [ 100 , 101 ]. However, each domain has been assessed independently and, therefore, the integration of the ICF domains into single measures is needed [ 102 ].…”
Section: Discussionmentioning
confidence: 99%